STRUCTURE ELUCIDATION OF BIOACTIVE ALKALOID COMPOUNDS ISOLATED FROM SPONGE Petrosia sp COLLECTED FROM BUNAKEN BAY MENADO - Gemini Alam; Puji Astuti; Subagus Wahyuono; Dinar Sari; Mark T Hamman (Indonesian Journal of Chemistry, 2005)
Two alkaloid compounds have been isolated from sponge Petrosia sp collected from Bunaken Bay Menado. These compounds have been found to inhibit several human cancer cell proliferation in vitro. Structure elucidation is needed to further characterize these bioactive compounds. The structure is determined by analyzing Ultra Violet (UV), Infra Red (IR), Mass Spectra (MS) and Nuclear Magnetic Resonance (NMR) spectra. Based on spectroscopic data, Thin Layer Chromatography (TLC) co-chromatograph with authentic samples and comparison with reported data the two compounds were identified as Manzamine A and 8-OH Manzamine A, respectively.